Keanekaragaman Spesies Lebah (Hymenoptera: Apidae) pada Berbagai Jenis Tanaman Berbunga di Kota Pagaralam Sumatera Selatan - Yulia Pujiastuti; Karen Uselbi Putri (Seminar Nasional Lahan Suboptimal, 2021)
Pujiastuti Y, Putri KU. 2021. Species diversity of bees (Hymenoptera: Apidae) on various types of flowering plants in Pagaralam City, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 603-610.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Bees are pollinating insects acting as pollinators on various kinds of plants, both cultivated plants, ornamental plants and wild plants. Bee visits to various plants can provide benefits for both parties, where bees get benefit from getting pollen and nectar as a source of food, while the infested plants get benefit from pollination assisted by bees. The purpose of research was to investigate bee species of Apidae family on various species of flowering plants in Pagaralam City. Surveys of Apidae bees have been carried out in three sub-districts of Pagar Alam City, South Sumatera, namely North Dempo District, South Pagaralam District and North Pagaralam District on 14 plant species spread over eight different villages. Observations were conducted from May to June 2021. Observations were carried out using scan sampling method (direct observation) and using insect net. At observation time, bees were taken using insect nets and put in a bottle vial for population count and identification purposes. Environmental parameters included temperature and humidity measured every time of observations, the morning air temperature (08.00-10.00) ranged from 21oC-27oC with air humidity of 73%-91%. It was found 4 species of bees belong to  the Apidae family namely A. dorsata, A. cerana, T. laeviceps, dan X. violace. Each of bee played a role as pollinators in various flowering plants observed.